Un caso empírico en la evaluación del riesgo de crédito de una institución de microfinanzas peruana - Lara Rubio, Juan (2011)
The growth of micro-credit along with the excellent conditions to carry out microfinance activity in the economy and financial system of the Republic of Peru are pushing for Microfinance Institutions (IMF) increased competition with banks in this segment business. Like in commercial banks, in microfinance questions such as: is this customer profitable?, What is the credit limit that I must accept to his/her application?, What interest rate should I charge to him/ her?, How I can reduce the risk default?, etc., are matters to be assessed properly. We propose a method that could facilitate improvement in customer qualification between failed and not failed. To this end, we propose a methodology that analyzes credit risk in the provision of microcredit through the design of a credit scoring model that we apply to a Development Agency for Small and Micro Enterprise (EDPYME), which is an IMF under the supervision by the Banking and Insurance Superintendency (SBS).